Observational Case Series Evaluation of the Granisetron Transdermal Patch System (Sancuso) for the Management of Nausea/Vomiting of Pregnancy - Le, Tran N.; Adler, Michael T.; Ouillette, Holly; Berens, Pamela; Smith, Judith A. (American Journal of Perinatology, 2017)
Objective The objective of this study was to observe the efficacy of antiemetic therapy (no emesis/retching episodes and no rescue medication use) when granisetron is administered via a transdermal patch system (TDS) in women who are 6 to 14 weeks pregnant when compared with oral ondansetron by evaluating the frequency of the use of rescue medications for control of nausea/vomiting of pregnancy (NVP).Methods This was an observational case series study to observe the potential benefits of granisetron TDS compared with oral ondansetron for management of NVP in pregnant patients during the first trimester. Dates of data collection were September 1, 2014, through December 31, 2015. There was no direct contact with patient. The oral ondansetron and granisetron TDS patients were matched by age, 4:1. The proportion of patients who received rescue antiemetics was calculated from those patients who continued to experience NVP. Risk factors for NVP were identified and compared between groups. Descriptive statistics were used to describe study results.Results Patients were prescribed rescue antiemetics in 0/3 patients in the granisetron TDS group compared with 2/12 patients in the oral ondansetron group.Conclusion Prospective efficacy studies on the use of granisetron TDS for management of NVP are needed to confirm this clinical observation.
Keywords: nausea/vomiting; pregnancy; antiemetics; granisetron; transdermal patch